Pengaruh Fermentasi Bakteri Asam Laktat Lactobacillus plantarum B307 Terhadap Kadar Proksimat dan Amilografi Tepung Taka Modifikasi (Tacca leontopetaloides) - Raden Haryo Bimo Setiarto; Nunuk Widhyastuti (Institut Pertanian Bogor, 2016)
Tacca (Tacca leontopetaloides) is plant that grows in coastal areas and high salinity, especially in the south coast of West Java. Tacca tubers have high content of carbohydrate, but it also contains some toxic compounds such as: taccaline, β – sitosterol, alcohol cerylic, and steroid sapogenin that are harmful for health. Fermentation on tacca tubers can change amylograph properties and proximate levels of modified tacca flour and reduce it toxic compounds. This study aimed at determining the effects of lactic acid bacteria (LAB) Lactobacillus plantarum B307 fermentation on the proximate levels and amylograph characteristics of modified tacca flour. Moisture and ash content of modified tacca flour still meet the requirements of SNI. Fermentation LAB Lactobacillus plantarum B307 led to increased levels of protein and lactic acid in the modified tacca flour, but it decreased pH value and carbohydrate content. Based on the analysis of amylograph, it can be concluded that tacca flour control without fermentation has the best gelatinization profile because it has good ability of setback viscosity.